Adult Memory T Cell Responses to the Respiratory Syncytial Virus Fusion Protein During a Single RSV Season (2018–2019) - Blunck, Brittani N.; Angelo, Laura S.; Henke, David; Avadhanula, Vasanthi; Cusick, Matthew; Ferlic-Stark, Laura; Zechiedrich, Lynn; Gilbert, Brian E.; Piedra, Pedro A. (Frontiers in Immunology, 2022)
Abstract Respiratory Syncytial Virus (RSV) is ubiquitous and re-infection with both subtypes (RSV/A and RSV/B) is common. The fusion (F) protein of RSV is antigenically conserved, induces neutralizing antibodies, and is a primary target of vaccine development. Insight into the breadth and durability of RSV-specific adaptive immune response, particularly to the F protein, may shed light on susceptibility to re-infection. We prospectively enrolled healthy adult subjects (n = 19) and collected serum and peripheral blood mononuclear cells (PBMCs) during the 2018–2019 RSV season. Previously, we described their RSV-specific antibody responses and identified three distinct antibody kinetic profiles associated with infection status: uninfected (n = 12), acutely infected (n = 4), and recently infected (n = 3). In this study, we measured the longevity of RSV-specific memory T cell responses to the F protein following natural RSV infection. We stimulated PBMCs with overlapping 15-mer peptide libraries spanning the F protein derived from either RSV/A or RSV/B and found that memory T cell responses mimic the antibody responses for all three groups. The uninfected group had stable, robust memory T cell responses and polyfunctionality. The acutely infected group had reduced polyfunctionality of memory T cell response at enrollment compared to the uninfected group, but these returned to comparable levels by end-of-season. The recently infected group, who were unable to maintain high levels of RSV-specific antibody following infection, similarly had decreased memory T cell responses and polyfunctionality during the RSV season. We observed subtype-specific differences in memory T cell responses and polyfunctionality, with RSV/A stimulating stronger memory T cell responses with higher polyfunctionality even though RSV/B was the dominant subtype in circulation. A subset of individuals demonstrated an overall deficiency in the generation of a durable RSV-specific adaptive immune response. Because memory T cell polyfunctionality may be associated with protection against re-infection, this latter group would likely be at greater risk of re-infection. Overall, these results expand our understanding of the longevity of the adaptive immune response to the RSV fusion protein and should be considered in future vaccine development efforts.